(untitled) (Revista horizonte, 2013)
Different factors affect sports performance, between these, within the spectrum of genetic, dermatoglyphics have constituted an element for guidance and sports selection using readings of skin marks. The objective of this research was to identify the dermatoglyphics profile of mapuche ethnicity athletes. Under a non-probability, descriptive, and mixed study design, 100 subjects (50 wmen and 50 men) aged 20 to 60 years old, of mapuche ethnicity, living in Temuco (Chile), with both surnames of mapuche ethnicity. We used the dermatoglyphic technique of Midlo Cummins. The results show a predominance of type â€œLâ€ footprints, oriented for strength and speed, along with a sport class III classification according to LQTS and D10. We conclude that mapuche subjects had a L type dermatoglyph, similar to those found in other ethnic groups with dark skin, and found in some sports strength and speed.